EFFECT OF FEED WITHDRAWAL AND ADDING DRIED BAKERY YEAST IN THE DIET ON DRESSING PERCENTAGES AND MEAT CHEMICAL COMPOSITION OF BROILERS: Shahrazad M. Al-Shadeedi , Maha A. AL-Hamiari ;Faris A. Al-Obaidi - Al-Shadeedi, Shahrazad M. (The Iraqi Journal of Veterinary Medicine, 2009)
This study has been conducted to study the effect of feed withdrawal (8 hours after slaughter) andadding dried bakery yeast on dressing percentage and meat chemical 45 marketed broiler chickens at 8weeks of age .The birds randomly distributed into three treatments (5 birds ) and each treatment tothree replicates (5 birds per replicate ) which were: un-treated control (T1) , broiler chickens subjectedto feed withdrawal 8 hrs. before slautered (T2) , broiler chickens fed a diet contained 1% of driedbakery yeast three days before subjected to feed withdrawal 8 hrs. before slaughtered (T3) . The dataobtained revealed the following :-Adding dried bakery yeast three days before subjected to feed withdrawal 8 hrs. beforeslaughtered (T3) significantly (p<0.01) decreased live body weight in the same time increased (p<0.01)carcass weight , dressing percentage with or without gibletts and gibletts percentage , also T3significantly (p<0.01) increased protein and decreased lipid and cholesterol of breast and legs meatcompaired with Feed withdrawal (T2) which significantly (p<0.01) predominent compaired with T1 .